As margens do rio no desenvolvimento de Goiânia: Meia Ponte, paisagens em transformação - Sakai, Diogo Isao Santos (2015)
Assessing the landscape of rivers in cities is the subject of this work, considering that, in most cases, banks and courses are transformed over time by the action of uses and harmful occupations, sublimating their identity and resulting in "residual space", according to Ferrara (2000). The degrading condition of urban fountains, at first glance, suggests the strangeness of landscape study, but imposes itself as one of the factors that required the extension of the term in contemporary (Cauquelin, 2007). The aesthetic perception becomes important from the relative seriousness of environmental issues in view of the progressive spatial degradation of streams, ponds, swamps, springs, beaches and rivers, for example, the Meia Ponte river route in Goiania. In the city, among the 85 water bodies that drain the territory of the metropolitan region there are only two rivers being one of them being the Meia Ponte, having their margins hit by high pollution levels(ANA, 2012). Even if in the past the fountain has represented reason for choosing the territory of the new capital Goias and subsequently their planning has been based on idealism preservationist system of green areas proposed by planners Attilio Corrêa Lima and Armando de Godoi (RIBEIRO, 2010), even bitterness titles as the seventh most corrupt spring of Brazil (ANA, 2011). The spatial perceptions, combined with the subsistence needs, possibly led man to elect the proximity to waterways one of the factors responsible for its fixation in the territory. Ironically, these days, this one is the reason for their estrangement. The different behaviors regarding the use of riverbanks express representing relationships in the social context of the place, acting decisively in the potentiation or limitation of its resources.